Satta Aparihāniya Dhamma for Social Peace and Harmony - Maharjan, Sunayana (Journal of Buddhist Studies (T.U.), 2025)
The Satta Aparihāniya Dhamma (SAD) provides teachings on ethical, moral, cultural, psychological and social aspects that aid in fostering peace and harmony. Harmony is defined as a state of agreement and understanding among individuals, groups and nations that everyone should possess as it fosters peace and reduces conflicts. Although the seven conditions of welfare are taught for the Vajjians by the Buddha, those principles are relevant to contemporary society and nation too for its development. The study focuses on the psychological aspect of SAD for developing peace and harmony. It is qualitative research where analytical and descriptive method has been implemented. The research findings show that SAD is crucial for the benefit of both the monastics and the laity. It serves as a timeless guide for conflict resolution, develop leadership qualities and by respecting and revering the senior citizens, women, religious leaders like Arhats and the preservation’s of cultural and spiritual values lead for peace and harmony in society.